Assessment of knowledge level and behavior about vaccines of mothers applying to the children's hospital - Topaktaş, Berkhan; Özdemir, Şule; Hasdemir, Sultan; Arslan, Hatice Nilden; Terzi, Ozlem; Dündar, Cihad (The European Research Journal, 2022)
Objectives: The aim of this study is to evaluate the knowledge levels of mothers who applied to a university hospital about childhood vaccinations and the sociodemographic characteristics affecting them. Methods: The population of the descriptive cross-sectional study consists of mothers who applied to the outpatient clinics of Ondokuz Mayıs University Children's Hospital between February 1 and March 31, 2019. A 32-item questionnaire developed by the researchers was applied to 338 mothers who agreed to participate in the study. Ethics committee and institution permissions were obtained. Data were presented with descriptive statistics. Results: Ninety-five point three percent of the mothers stated that the vaccine was necessary. While 52.7% of the individuals stated that they were aware of the existence of self-paid vaccines, it was determined that 84.0% of the participants did not have self-paid vaccines for their children. Thirty-seven point six of the participants knew that the first vaccine of the newborn was given at birth. Healthcare staffs were among the sources of information for 94.7% of the mothers who stated that they received information about vaccination. Conclusions: It was found out that the mothers had information about the vaccine. However, the rate of vaccination other than routine vaccines was low. In order to combat vaccine refusals and prevent misinformation, it is considered to be important to provide information at every opportunity, and especially about paid vaccines, parents should be given more information.